Non-sedating benzodiazepines cause paralysis and tissue damage in the parasitic blood fluke Schistosoma mansoni. - Paul McCusker; Md Yeunus Mian; Guanguan Li; Michael D Olp; V V N Phani Babu Tiruveedhula; Farjana Rashid; Lalit Kumar Golani; Ranjit S Verma; Brian C Smith; James M Cook; John D Chan (Public Library of Science (PLoS), 2019)
Parasitic flatworm infections (e.g. tapeworms and fluke worms) are treated by a limited number of drugs. In most cases, control is reliant upon praziquantel (PZQ) monotherapy. However, PZQ is ineffective against sexually immature parasites, and there have also been several concerning reports on cestode and trematode infections with poor PZQ cure-rates, emphasizing the need for alternative therapies to treat these infections. We have revisited a series of benzodiazepines given the anti-schistosomal activity of meclonazepam (MCLZ). MCLZ was discovered in the 1970's but was not brought to market due to dose-limiting sedative side effects. However, in the decades since there have been advances in our understanding of the benzodiazepine GABAA receptor sub-types that drive sedation and the development of sub-type selective, non-sedating ligands. Additionally, the sequencing of flatworm genomes reveals that parasitic trematodes and cestodes have lost GABAAR-like ligand gated anion channels, indicating that MCLZ's anti-parasitic target is distinct from the human receptors that drive sedation. Therefore, we have screened a library of classical and non-sedating 1,4-benzodiazepines against Schistosoma mansoni and identified a series of imidazobenzodiazepines that immobilize worms in vitro. One of these hits, Xhe-II-048 also disrupted the parasite tegument, resulting in extensive vacuole formation beneath the apical membrane. The hit compound series identified has a dramatically lower (~1000×) affinity for the human central benzodiazepine binding site and is a promising starting point for the development of novel anti-schistosomal benzodiazepines with minimal host side-effects.